2019
DOI: 10.2967/jnumed.118.220590
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence in Nuclear Medicine

Abstract: Despite the great media attention for artificial intelligence (AI), for many health care professionals the term and the functioning of AI remain a "black box," leading to exaggerated expectations on the one hand and unfounded fears on the other. In this review, we provide a conceptual classification and a brief summary of the technical fundamentals of AI. Possible applications are discussed on the basis of a typical work flow in medical imaging, grouped by planning, scanning, interpretation, and reporting. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
71
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(77 citation statements)
references
References 67 publications
0
71
0
6
Order By: Relevance
“…The use of data mining in the analysis of medical data is currently becoming a popular issue. Data mining methods are applied in order to use various data obtained from medical examinations in the diagnosis of diseases [21]. In this respect, data mining can be defined as the work of extracting implicit information of value among large-scale data [31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of data mining in the analysis of medical data is currently becoming a popular issue. Data mining methods are applied in order to use various data obtained from medical examinations in the diagnosis of diseases [21]. In this respect, data mining can be defined as the work of extracting implicit information of value among large-scale data [31].…”
Section: Discussionmentioning
confidence: 99%
“…In order to classify diseases using diagnostic data, it is necessary to create a model that reveals hidden patterns in these data sets. Entropy-based methods, logistic regression models, Bayesian classifiers, and artificial neural networks are the commonly used classification methods [21][22][23]31,33]. The classification rules that are formed by applying these methods on training data are then applied to test data in order to predict the class of each subject.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AI and ML may aid medical imaging-based diagnosis, not only in terms of the detection of disease, but also in management, reporting, and prognostication. [1] ANN is a computational model of ML based on the human brain. It has been found that ANN are powerful tools for pattern recognition, signal processing, image or speech data compression, and learning expert systems.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the rapid progress of machine learning in the interpretation of medical images, dire predictions have been made about the future of radiology as a clinical discipline (7-9). Nensa et al focus on the use case ''nuclear medicine'' for artificial intelligence, highlighting associated challenges but also opportunities (10). As a consequence of the advances in algorithms, deep learning, computing power, and the introduction of digital PET allowing for fast dynamic image acquisition trigger the hope of finding clinical evidence and relevance for radiomics.…”
mentioning
confidence: 99%